Recent Currents in Research on the Prophetic Literature - Tiemeyer, Lena-Sofia (The expository times, 2008)
This article outlines the main directions that scholarly research on the biblical prophetic literature has taken in the last twenty years. First, it provides an overview of current studies that, benefiting from the insights of sociology, anthropology and Ancient Near Eastern studies, enhance our understanding of the prophetic roles in Ancient Israel. Secondly, it gives examples of recent developments in the areas of rhetorical criticism, source criticism and redaction criticism pertaining to the prophetic literature. Lastly, it offers a glimpse of some of the currently hotly debated issues arising from the prophetic literature.